Implicações do terceiro setor no debate da gestão democrática: um estudo a partir do programa "Amigos da Escola" - GARCIA, Mauricio Luis Silva (2009)
This research had as objective to analyze the politics of incentive to the participation of the community in the pertaining to school management as an instrument of democratization of the management from the partnerships firmed with organizations of the third sector. I defined as study object the Program “Friends of the School”. I made the analysis of this Program, estimated its, practical its and its joint with the debate around the democratic management. Such object appears in the context of redefinition of strategies of social participation and models of management of the public institutions from the productive reorganization of the capital. In this way, I took as starting point the following question: of that it forms the actions of the partnerships they redefine the paper of the State, of the civil society, modifying the dispute around thesocial control of the public thing? Therefore, the analysis that I considered required an adequate methodology to this study. The type of adopted study was the critical study of documents of reference of the Program “Friends of the School”. I chose the documentary research as the strategy of collection of data. As research source, I analyze cartload of orientation of the Program “Friends of the School” for the participation of volunteers and of the formation of voluntary managers. These sources had allowed a qualitative analysis of the chosen concepts as categories, amongst which I present: social control, democratic management, participation and autonomy. Such Program stimulates a participation meaning in the terms of a non-political and appointment voluntary solidarity with the quality of the education. Also it allows to affirm an absence me of social control on the part of the pertaining to school community.